2012
DOI: 10.5755/j01.ms.18.2.1922
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Strength of Textile Bonded Seams

Abstract: The strength of the textile bonded seams was analyzed. Two or more fabric layers joining are based on use of base layers structural properties and thermoplastic properties of adhesive film used for bonding. Five commercial produced fabrics of different structure (woven, knitted, laminate) and fiber content (polyester, cotton, flax) were used in this experiment. Thermoplastic polyurethane film was transferred from the base of silicone to fabric using 160 °C temperature and 10 seconds pressing duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…The literature reviews concerning weld-line formation on textiles mainly focus on the qualities of the welded seams. For instance; in their study Kakubčionienė et al examined the qualities of hot welded seams using the thermoplastic type and reported that the qualities of fabric bonding depend on proper selections of parameters during the two bonding stages: film transfer and layer bonding [10]. In addition, they stated that bonding strength depends on structure type, bearing surface and treatment and a bonding problem can appear when using teflon and silicon finishes.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reviews concerning weld-line formation on textiles mainly focus on the qualities of the welded seams. For instance; in their study Kakubčionienė et al examined the qualities of hot welded seams using the thermoplastic type and reported that the qualities of fabric bonding depend on proper selections of parameters during the two bonding stages: film transfer and layer bonding [10]. In addition, they stated that bonding strength depends on structure type, bearing surface and treatment and a bonding problem can appear when using teflon and silicon finishes.…”
Section: Introductionmentioning
confidence: 99%
“…welding process parameters using hot air: pressure, temperature, velocity) as well as compatibilities of materials with welding techniques. [21][22][23][24][25][26] Research is currently being conducted on the formation of a new type of textile transmission line with an insulation layer using hot air welding technologies. In order to manufacture textile transmission lines, different welding parameters with different conductive yarns and welding tapes are considered in order to obtain flexible textile signal transmission lines that are reliable and durable in functionality while preserving the textiles' aspects.…”
mentioning
confidence: 99%
“…The heat temperature in this pre-molding test was set as 160°C, 170°C, and 180°C, respectively. [31][32][33][34][35] Each kind of fabric was tested 10 times. The experiment was processed under standard room conditions of 21 ± 1°C and 65 ± 2% relative humidity (RH), and all the subsequent experiments were conducted under this condition as well.…”
Section: Experimental Phasesmentioning
confidence: 99%